Pengaruh inflasi, suku bunga dan pembiayaan bank syariah terhadap ekspor Indonesia - Muhammad Ikhsan Harahap; Sugianto Sugianto (Jurnal Riset AKuntansi dan Bisnis, 2023)
Indonesia's exports are susceptible to changes due to various factors. Therefore it is necessary to do research to see what factors influence Indonesia's exports.This article aims to elaborate the influence of inflation, interest rate and Islamic Bank Financing on Indonesia’s exports. This study uses a quantitative method using secondary data obtained from Central Bureau of Statistics (BPS),  The Financial Services Authority (OJK) and Bank Indonesia ( BI). Data analysis using multiple linear regression method. The results indicate that inflation and Islamic Bank Financing influenced on exports, meanwhile interest rate had no influenced on Indonesia’s export